Use of wearable devices in the teaching-learning process: a systematic review of the literature - Glasserman-Morales, Leonardo David; Carlos-Arroyo, Martina; Ruiz-Ramirez, Jessica Alejandra; Alcantar-Nieblas, Carolina (Frontiers in Education, 2023)
Multimodal Learning Analytics (MMLA) has emerged as an encompassing approach to data collection, facilitating the analysis of student interactions across a variety of resources. MMLA capitalizes on data gleaned from diverse interactions, utilizing wearable devices to track physiological responses. This yields deeper insights into factors such as cognitive load, stress levels, interest, and other stimuli pivotal to the learning process. Nonetheless, it is crucial to acknowledge the theoretical and practical challenges underpinning the integration of wearable devices into learning experiences, both in academic settings and in everyday life activities. A systematic review of literature (SLR) was conducted with the aim of identifying the characteristics of studies that incorporate wearable devices into teaching-learning process analyses. The outcomes enabled us to discern key attributes such as participant descriptions, the activities implemented for data collection, a broad spectrum of biometric indicators -with electrodermal activity (EDA) and heart rate (HR) among the most commonly used, and methodologies employed in data analysis. Future endeavors should be centered on the formation of interdisciplinary teams. The objective is to devise novel methodologies for multimodal data collection and analysis that can discern performance variables, thereby enhancing learning in a manner conducive to more fluid, reflective educational experiences for all participants in the teaching-learning process.